2D expulsion and migration modelling of the stratigraphic profile no. 210320-2056 through the Hammerfest Basin, south-western Barents Sea - Zięba, Krzysztof (My University, 2012)
The 2D basin modelling of the geological profile number 210320-2056 has been carried out. The profile is localized in the Hammerfest Basin, south-western Barents Sea. The thesis aims are to evaluate quantitatively and qualitatively hydrocarbon accumulations and source rock potential. It considers also the Cenozoic exhumation impact on the migration patterns. The approach tests two heat flow models, which have been published by Cavanagh et al. (2006) and Roufosse (1987).

Praca magisterska obejmuje modelowanie 2D profilu stratygraficznego numer 210320-2056. Profil ten zlokalizowany jest w Hammerfest Basin, południowo-zachodniej części Morza Barentsa. Praca obejmuje ilościową oraz jakościową ewaluację akumulacji węglowodorów oraz określa potencjał skał źródłowych. Niniejszy projekt porusza ponadto wpływ kenozoicznego podnoszenia obszaru Morza Barentsa na migrację węglowodorów. W niniejszej pracy zostały porównane również dwa różne modele strumienia ciepła stworzone przez Cavanagh et al. (2006) oraz Roufosse (1987).
Modelowanie 2D ekspulsji i migracji profilu stratygraficznego numer 210320-2056 w Hammerfest Basin, południowo-zachodnie Morze Barentsa
Keywords: 2D basin modelling; modelowanie 2D; Hammerfest Basin; baseny sedymentacyjne; Hammerfest Basin